Effectiveness of an ACT‐based rehabilitation program for the treatment of chronic fatigue: Results from a 12‐months longitudinal study. Issue 1 (3rd August 2020) - Brugnera, Agostino; Nordstrand Jacobsen, Trym; Woodhouse, Astrid; Compare, Angelo; Børsting Jacobsen, Henrik
Abstract : Acceptance and Commitment Therapy (ACT) is potentially effective for treating chronic fatigue. Given the paucity of studies on this topic, we aimed to assess long‐term trajectories of primary (fatigue, quality of life and functional abilities) and secondary outcomes (anxious and depressive symptoms) of an ACT‐based rehabilitation program for patients with chronic fatigue. Further, we examined if changes in potential process variables (psychological inflexibility, metacognitive beliefs, and cognitive and behavioral responses to symptoms) during ACT predicted change in all outcomes across follow‐up. One‐hundred ninety‐five workers on sick leave (mean age: 43.61 ± 9.33 years; 80.5% females) with a diagnosis of chronic fatigue were enrolled in a manualized, 3.5‐week intensive return‐to‐work rehabilitation program based on ACT. All completed a battery of questionnaires at pre‐, post‐treatment, 6 and 12 months follow‐up. We found significant longitudinal changes in most primary and secondary outcomes from pre‐ up to 12 months follow‐up. All process variables significantly decreased from pre‐ up to 12 months follow‐up, and pre‐to‐post changes in fear avoidance beliefs were most often associated with a greater change in outcomes across follow‐up. Depressive symptomatology showed a similar trajectory of change to fatigue, meaning that scores were correlated at each time point and tended to converge over time. This suggests that both symptoms influence each other substantially over a year following the treatment. Concluding, results lend support to the effectiveness of an ACT‐based rehabilitation program for patients with chronic fatigue and provide preliminary evidence for the role of process variables and depressive symptomatology on subsequent change in outcomes.